Chronic pericarditis and recurrent pericardial effusion of unknown origin in a kitten: a case report - Weingand, Nicole; He, Chang; Grau-Roma, Llorenç; Adamik, Katja-Nicole (Frontiers in Veterinary Science, 2024)
A three-month-old kitten was presented after successful cardiopulmonary resuscitation including a presumed intracardial injection by its primary care veterinarian. Throughout the subsequent hospitalization in the intensive care unit the cat exhibited recurrent hemorrhagic pericardial effusions, along with concurrent pleural and abdominal effusions, resulting in multiple clinical deteriorations, necessitating pericardio-and thoracocenteseses. Despite more than 3 days of intensive care, the cat experienced another cardio-pulmonary arrest with unsuccessful attempts to achieve return of spontaneous circulation. Necropsy and histopathological findings revealed a diffuse chronic-active pericarditis and hemorrhagic pericardial effusion, a condition that has not been documented in the context of cardiopulmonary resuscitation or pericardiocentesis.